High strain rate behavior of magnesium alloys AZ 31B under dynamic tensile loading - Hensen Jaya Kesuma. (2011)
Magnesium alloy has been widely used nowadays especially in the automotive and aerospace industry due to its high specific strength with lower density, two third the density of aluminum alloy. A research has been conducted that by using magnesium alloy instead of aluminum alloy or stainless steel can help reduce the fuel emission which is one of the major problems faced by these industries.